PeopleSoft PeopleTools tips & techniques [ - Marion, Jim J. (McGraw-Hill, 2010)
"Maximize the efficiency and productivity of your PeopleSoft applications from Oracle using the proven methods and best practices in this Oracle Press guide. PeopleSoft PeopleTools Tips & Techniques lays out the benefits of each tactic along with implementation considerations, programming instructions, and reusable code samples. Construct powerful iScripts, build custom UIs, work with Java and Ajax, and integrate the latest Web2.0 features. Test-driven development, application security, performance tuning, and debugging are also covered in this authoritative resource."--Resource description p